Due Process and the Obligation to Deliver SPDP: Implementation of Constitutional Court Decision No. 130/PUU-XIII/2015 - Wijaya, Didit Wijayanto; Sirait, Timbo Mangaranap; Wibowo, Basuki Rekso (Research Horizon, 2025)
Constitutional Court Decision Number 130/PUU-XIII/2015 mandates investigators to deliver the Investigation Commencement Notification to public prosecutors, reported persons, and victims within seven days after the issuance of the investigation order. This obligation aims to guarantee legal certainty and protect the constitutional rights of suspects as stipulated in Article 28D paragraph (1) and Article 28I paragraph (2) of the 1945 Constitution. This study examines the legal consequences of procedural violations in delivering Investigation Commencement Notifications on the validity of suspect designation and investigation processes. The research methodology employs a normative juridical approach with analysis of legislation, court decisions, and legal doctrines. The discussion focuses on the ratio decidendi of the Constitutional Court Decision, investigator obligations within the integrated criminal justice system, and pretrial mechanisms as juridical controls. The research finds that procedural violations in delivering Investigation Commencement Notifications result in the nullification of investigations and suspect designations due to contradiction with due process of law principles. Administrative and criminal sanctions for investigators who violate the obligation to deliver Investigation Commencement Notifications are necessary to strengthen constitutional rights protection of suspects within Indonesia’s criminal justice system.